Schwann cells apoptosis is induced by high glucose in diabetic peripheral neuropathy - Liu, Yu-pu; Shao, Shui-jin; Guo, Hai-dong (Life sciences (1973), 2020)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus that affects approximately half of patients with diabetes. Current treatment regimens cannot treat DPN effectively. Schwann cells (SCs) are very sensitive to glucose concentration and insulin, and closely associated with the occurrence and development of type 1 diabetic mellitus (T1DM) and DPN. Apoptosis of SCs is induced by hyperglycemia and is involved in the pathogenesis of DPN. This review considers the pathological processes of SCs apoptosis under high glucose, which include the following: oxidative stress, inflammatory reactions, endoplasmic reticulum stress, autophagy, nitrification and signaling pathways (PI3K/AKT, ERK, PERK/Nrf2, and Wnt/β-catenin). The clarification of mechanisms underlying SCs apoptosis induced by high glucose will help us to understand and identify more effective strategies for the treatment of T1DM DPN. [Display omitted]